Analysis of Psychological Problems in People with HIV/AIDS - Roza, Defia (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
HIV/AIDS is a disease that attacks the immune system, which causes opportunistic infections. In addition to physical problems, many experience psychological disorders which further reduce the quality of life of PLWHA. This study aims to analyze psychological problems in PLWHA. The design of this research was an observational descriptive study with a population of PLWHA who visited VCT polyclinic at M.Djamil Hospital, Padang. A sample of 50 respondents was selected using a purposive sampling technique. The inclusion criteria were HIV patients who were willing to participate and the exclusion criteria were patients who had opportunistic infections and severe drug side effects. Data collection was carried out by interviewing and using a questionnaire. The results of this study found that the most negative experience that occurred were receiving stigma and negative behavior from society (62%), having experienced violence (54%) and being MSM (52%). The most common negative thoughts are fear of social stigma (84%), fear of dying in severe AIDS (70%), and fear of death (64%). The most common negative behaviors were depression (66%), staying away from other people (64%), being lazy at school (54%), and wanting to commit suicide (46%). It is hoped that health workers will be able to overcome the psychological problems experienced by PLWHA with appropriate therapy.